The Relation of a Subject and Object of Scientific Research in the Light of Critical Philosophy of I. Kant - Vitaly Aleksandrovich Volkov (North-West institute of management of the Russian Presidential Academy of National Economy and Public Administration, 2018)
The article deals with the definition and relationship of subject and object. The critical philosophy of Kant is content, in which there is substantiation and necessity of a permission problem.